Genomic profiles of vaccine breakthrough SARS-CoV-2 strains from Odisha, India. (June 2022) - Ghosh, Arup; Walia, Safal; Rattan, Roma; Kanampalliwar, Amol; Jha, Atimukta; Aggarwal, Shifu; Fatma, Sana; Das, Niyati; Chayani, Nirupama; Prasad, Punit; Raghav, Sunil K.; Parida, Ajay
Highlights: Out of 36 samples, 33 reported symptomatic breakthrough infections Predominant presence of T478K and L452R mutation in spike protein The majority of the patients were infected with the Delta (B.1.617.2) variant S:EFR156G substitution observed in 10 breakthrough cases Only one case with comorbidities reported hospitalization